Kontribusi Corporate Governance Dalam Mengurangi Kecurangan Laporan Keuangan - Arief Mulyadianto; Dwi Jaya Kirana; Aniek Wijayanti (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
This research was conducted to test and find out the role of corporate governance in reducing financial statement fraud. The variables used in this study are the performance of the board of commissioners, audit committee financial expertise, and institutional ownership as an independent variable and for the dependent variable using fraudulence financial statements with the Beneish M-Score proxy. The sample used in this study is manufacturing companies listed on the Indonesia Stock Exchange. The analysis technique used uses SPSS with a significance level of 5%. The results of this study are the performance of the board of commissioners, audit committee financial expertise and institutional ownership does not affect reducing fraudulence financial statements. Keywords: the performance of the board of commissioners, audit committee financial expertise, institutional ownership, fraudulence financial statements, beneish m-score.